2022
DOI: 10.1037/h0101872
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of everyday prospective memory performance: A superiority in the execution of event-based tasks over time-based tasks reverses in real-life situations.

Abstract: Prospective memory (PM) involves remembering intended actions in response to a target event or at a particular time. Both the PM theories and laboratory-based studies suggest that event-based tasks are less difficult to perform. The present study investigated whether the superior performance of event-based tasks generalizes to real-life intentions, and examined the relationships between the intention completion and various characteristics of daily living, for example, busyness, routine, affect, and stress. Eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 43 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…To examine the role of monitoring processes in appointment attendance, we measured participants' perceived importance of attending. Similar to previous work on the benefits of higher perceived importance on PM performance (e.g., Andrzejewski et al, 1991; Ihle et al, 2012; Niedźwieńska et al, 2013; Szarras & Niedźwieńska, 2011; Wójcik et al, 2022), we predicted that Show participants would perceive attendance as more important than No‐Show participants. We were also interested in whether Show participants would report fewer instances of everyday PM failures compared to No‐Show participants, thereby suggesting overall better memory in daily life.…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…To examine the role of monitoring processes in appointment attendance, we measured participants' perceived importance of attending. Similar to previous work on the benefits of higher perceived importance on PM performance (e.g., Andrzejewski et al, 1991; Ihle et al, 2012; Niedźwieńska et al, 2013; Szarras & Niedźwieńska, 2011; Wójcik et al, 2022), we predicted that Show participants would perceive attendance as more important than No‐Show participants. We were also interested in whether Show participants would report fewer instances of everyday PM failures compared to No‐Show participants, thereby suggesting overall better memory in daily life.…”
Section: Introductionsupporting
confidence: 72%
“…Examining self-reported strategy use revealed that proportionately more Show than No-Show participants used strategies to remember their appointments, supporting the notion that control processes, like strategy use, promote appointment attendance (Ihle et al, 2012;W ojcik et al, 2022). Importantly, it may not be the number of strategies but the types of implemented strategies that distinguish those who remember to attend their appointments.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations